Executive power eaudiobook - Flynn, Vince (Mitch Rapp, 2003)
CIA super-agent Mitch Rapp battles global terrorism in a high-octane follow-up to the New York Times best-selling Separation of Power. Transporting us into an intriguing geopolitical puzzle full of deadly motives, covert operatives, and all the true-to-life insider detail we've come to expect from Vince Flynn, Executive Power is a high-flying story that delivers shattering suspense with the velocity of a 9mm bullet.